2018
DOI: 10.3389/feart.2018.00064
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Surface Temperatures on a Debris-Covered Glacier With an Unmanned Aerial Vehicle

Abstract: A layer of debris cover often accumulates across the surface of glaciers in active mountain ranges with exceptionally steep terrain, such as the Andes, Himalaya, and New Zealand Alps. Such a supraglacial debris layer has a major influence on a glacier's surface energy budget, enhancing radiation absorption, and melt when the layer is thin, but insulating the ice when thicker than a few cm. Information on spatially distributed debris surface temperature has the potential to provide insight into the properties o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
82
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(109 citation statements)
references
References 59 publications
2
82
0
1
Order By: Relevance
“…Indeed, a recent study by Abolt et al () reported similar issues of temperature drift with both the FLIR Tau 2 sensor (upon which the DJI Zenmuse XT camera used in this study is based) and also the FLIR Vue Pro sensor, indicating that this problem is both (a) relatively common and (b) not limited to one particular camera model. Similarly, recent work with sUAS‐TIR imaging of glacier temperatures revealed temperature drift of a comparable magnitude using a SenseFly ThermoMap TIR camera, albeit under very different environmental conditions (Kraaijenbrink et al, ). During the current study, we tested three versions of the same camera, which all generated very similar results, emphasising that observed drift was not an artefact of a single faulty camera.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Indeed, a recent study by Abolt et al () reported similar issues of temperature drift with both the FLIR Tau 2 sensor (upon which the DJI Zenmuse XT camera used in this study is based) and also the FLIR Vue Pro sensor, indicating that this problem is both (a) relatively common and (b) not limited to one particular camera model. Similarly, recent work with sUAS‐TIR imaging of glacier temperatures revealed temperature drift of a comparable magnitude using a SenseFly ThermoMap TIR camera, albeit under very different environmental conditions (Kraaijenbrink et al, ). During the current study, we tested three versions of the same camera, which all generated very similar results, emphasising that observed drift was not an artefact of a single faulty camera.…”
Section: Discussionmentioning
confidence: 71%
“…It is possible that greater drift results from insufficient insulation (or shielding) from external influences in comparison with larger TIR cameras. However, we also hypothesise that camera miniaturisation necessitates closer mounting of electronic components, potentially resulting in increased heat build-up (e.g., Kraaijenbrink et al, 2018;Ribeiro-Gomes et al, 2017) and thus greater temperature drift in comparison with larger TIR cameras. This presents a continued challenge for sUAS-based TIR imagery acquisition.…”
Section: Quantification Of Discrete Thermal Inputs (Onondaga Creek)mentioning
confidence: 99%
See 1 more Smart Citation
“…They are a particularly attractive tool for glaciological research due to their ability to collect data over wider areas and inaccessible regions of glaciers, with relatively low costs and efforts. As a result, there have been several recent glaciological studies relying on UAV data [7,[10][11][12][13][14][15][16][17][18]. Most commonly, these studies are using imagery in the visual spectrum from UAV-mounted digital cameras and SfM to recreate glacier surfaces and track motion.…”
Section: Introductionmentioning
confidence: 99%
“…Most commonly, these studies are using imagery in the visual spectrum from UAV-mounted digital cameras and SfM to recreate glacier surfaces and track motion. Glaciological studies using UAVs have tracked glacier motion (e.g., [7,10,14]); measured seasonal or multi-year melt (e.g., [7,10,13]); analyzed calving and crevasse dynamics (e.g., [12,15,16]); and mapped surface characteristics such as drainage networks [11], albedo [17], debris cover [18], and cryoconite holes [19].…”
Section: Introductionmentioning
confidence: 99%